The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jpcb.9b11597
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Nanoluciferase–Furimamide Complex: A Theoretical Study on Different Protonation States

Abstract: Luminescence of furimamide is 150 times brighter than oxidized luciferins in firefly and renilla luciferase. However, we do not have a clear understanding of the structure, function, and dynamic behavior of the nanoluciferase−furimamide complex. Here, for the first time, the absorption and emission properties of eight different possible light emitter forms of furimamide were investigated using the time-dependent density functional theory (TD-DFT) method in the gas phase and aqueous solution. The emission oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The docking procedure involved an empirical free energy function and the Lamarckian genetic algorithm (LGA). 49 Prior to docking, the protein was prepared by adding hydrogen atoms and Gasteiger charges. Docking grid box dimensions of 70 × 70 × 70 points with a grid spacing of 0.375 Å were defined around the binding site.…”
Section: Molecular Docking Methodsmentioning
confidence: 99%
“…The docking procedure involved an empirical free energy function and the Lamarckian genetic algorithm (LGA). 49 Prior to docking, the protein was prepared by adding hydrogen atoms and Gasteiger charges. Docking grid box dimensions of 70 × 70 × 70 points with a grid spacing of 0.375 Å were defined around the binding site.…”
Section: Molecular Docking Methodsmentioning
confidence: 99%
“…The NLuc reaction mechanism is still undiscovered; however, as Gaussia luciferase (GLuc) bears the most resemblance to NLuc due to its substrate, size, and marine origin, the reaction mechanism may contain a similarity as well. [5][6][7] Some studies have reported this enzyme in a split scheme with two or three inactive fragments that are illuminated only by close proximity. The well-known two-part split NLuc, NanoLuc Binary Technology (NanoBiT), 9 is used widely in diversied technology.…”
Section: Introductionmentioning
confidence: 99%
“…Since obtaining and elucidating the structure, as well as achieving the synthesis of the luciferin substrate (LUC, Scheme ) by Bitler et al and White et al in the late 1950s, , extensive experimental and theoretical research has been conducted to understand the mechanism involved in the efficient bioluminescence (BL) of Photinus pyralis. , The study of BL in general benefits from computational simulations of entire systems, as well as from working with chemiluminescence (CL) reactions that serve as comprehensive models and analogues of BL processes. , …”
Section: Introductionmentioning
confidence: 99%